2016
DOI: 10.1161/jaha.115.002447
|View full text |Cite
|
Sign up to set email alerts
|

Area Median Income and Metropolitan Versus Nonmetropolitan Location of Care for Acute Coronary Syndromes: A Complex Interaction of Social Determinants

Abstract: BackgroundMetropolitan versus nonmetropolitan status and area median income may independently affect care for and outcomes of acute coronary syndromes. We sought to determine whether location of care modifies the association among area income, receipt of cardiac catheterization, and mortality following an acute coronary syndrome in a universal health care system.Methods and ResultsWe studied a cohort of 14 012 acute coronary syndrome patients admitted to cardiology services between April 18, 2004, and December… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 37 publications
1
10
0
Order By: Relevance
“…Of the 19 included studies, 8 reported short-term (within 30 days of AMI) mortality, 11 , 16 , 22 , 23 , 24 , 25 , 26 , 27 10 reported on intermediate (31 days to 1 year) mortality, 11 , 21 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 and 4 reported on long-term mortality (> 1 year) post AMI. 11 , 32 , 33 , 34 Twelve studies reported on catheterization post-AMI, 11 , 16 , 21 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 35 , 36 and 9 on revascularization. 11 , 16 , 25 , 26 , 29 , 30 , 32 , 36 , 37 Four studies examined referral to or participation in cardiac rehabilitation.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Of the 19 included studies, 8 reported short-term (within 30 days of AMI) mortality, 11 , 16 , 22 , 23 , 24 , 25 , 26 , 27 10 reported on intermediate (31 days to 1 year) mortality, 11 , 21 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 and 4 reported on long-term mortality (> 1 year) post AMI. 11 , 32 , 33 , 34 Twelve studies reported on catheterization post-AMI, 11 , 16 , 21 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 35 , 36 and 9 on revascularization. 11 , 16 , 25 , 26 , 29 , 30 , 32 , 36 , 37 Four studies examined referral to or participation in cardiac rehabilitation.…”
Section: Resultsmentioning
confidence: 99%
“…Eleven studies included Ontario populations, 11 , 21 , 24 , 30 , 31 , 32 , 33 , 35 , 37 , 38 , 39 4 were from Alberta, 25 , 27 , 28 , 34 2 were from Quebec 26 , 36 and 2 included patients from more than 4 provinces 16 , 29 ( Table 1 ). Several patient cohorts overlapped across studies.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations